INTERNALISASI NILAI-NILAI AL-QUR’AN TERHADAP ILMU DAN PENDIDIKAN DALAM ISLAM - Sirajuddin Zar (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2017)
Islam is a religion that concerned to all aspects of life. Everything has been arranged in accordance with a command from Allah. Religion in Islamic view is a basic principle and a way of life and tawhid is the basis of everything. Islamic science focused on how Islam as the foundation of science that binding value and science based on the framework of tawhid which containing three components, namely, theocentric, anthropocentric and cosmocentric and those components become the basis for the character education in Islam